Mungbean and pumpkin protein isolates as novel ingredients for the development of meat analogs using heat-induced gelation technique - Baig, Mohammad Affan; Ajayi, Feyisola Fisayo; Mostafa, Hussein; Sivapragasam, Nilushni; Maqsood, Sajid (Frontiers in Sustainable Food Systems, 2023)
Mungbean and pumpkin are rich source of proteins and nutrients which could be utilized in novel food formulations. This study involves formulation of meat analog using mungbean protein isolate (MBPI) and pumpkin protein isolates (PPI) through optimization process using Box–Behnken Design (BBD) of response surface methodology (RSM). MBPI and PPI were used as base ingredients for the development of meat alternatives using an innovative heat-induced gelation process. Methylcellulose (MC) and gum Arabic were used as supporting matrices for obtaining desired texture of the meat analog. The emulsifying activity, water-holding capacity, and oil-holding capacity of MBPI and PPI were analyzed. The set of physicochemical response factors used in RSM was moisture content, protein content, color, and textural properties of the formulated meat analogs. The selected independent variables were set at three levels (−1, 0, 1) with protein ratio (20:10, 15:15, and 10:20 of MBPI-PPI), Water (32, 37, and 42%), and MC (5, 6, and 7%). RSM results showed that the model effectively described the correlation between the independent variables (protein ratio, water percentage, and MC percentage) and the response factors. The microstructure of the analog showed porous and fibrous structures. It was observed that the degree of cross-linking between protein molecules could have impacted the textural properties that were associated with viscoelastic characteristics as reflected in the rheological analysis. Overall, the study shows that the mungbean and pumpkin seed proteins could be utilized as a potential ingredient to improve the textural properties of the meat analog, while it is also recommended to explore such proteins with other mechanical processing techniques like extrusion.